2005
DOI: 10.1177/1073191105278740
|View full text |Cite
|
Sign up to set email alerts
|

Construct Validity of the Balloon Analog Risk Task (BART)

Abstract: To continue research assessing the validity of the Balloon Analog Risk Task (BART) as a measure of risk taking, the BART was administered to a nonforensic sample of individuals with varying levels of psychopathic characteristics. Construct validity of the BART was evaluated by measuring risk-taking behavior in relation to self-reported psychopathy, anxiety, psychophysiological data, and demographic variables. Supporting the construct validity of the BART, while controlling for variance accounted for by interre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
154
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 198 publications
(163 citation statements)
references
References 77 publications
(126 reference statements)
3
154
0
2
Order By: Relevance
“…The same study also found BART performance to be associated with deficiencies in behavioral constraint in adults (Lejuez et al, 2002). In a sample of young adults, antisocial behavior measures were positively correlated with risk-taking on the BART (Hunt et al, 2005). In a study differentiating smokers from nonsmokers, the BART was more effective than the Iowa Gambling Task (Lejuez et al, 2003a).…”
Section: Introductionmentioning
confidence: 78%
“…The same study also found BART performance to be associated with deficiencies in behavioral constraint in adults (Lejuez et al, 2002). In a sample of young adults, antisocial behavior measures were positively correlated with risk-taking on the BART (Hunt et al, 2005). In a study differentiating smokers from nonsmokers, the BART was more effective than the Iowa Gambling Task (Lejuez et al, 2003a).…”
Section: Introductionmentioning
confidence: 78%
“…The SRP9II was designed to parallel the PCL9R model of psychopathy using self9report. Hunt et al (2005) found correlations between risk9taking on the BART and Factor 2 ("Antisocial Behavior") of the SRP9II. These two studies offer conflicting findings regarding the relationship between the BART and psychopathy, although notably across two different samples.…”
mentioning
confidence: 87%
“…Hence, one might expect risk9taking behavior on the BART from an individual who shows high scores on the Disinhibition subscale. Further, Hunt et al (2005) found a relationship between SRP9II factor two (antisocial behavior) and the BART. Hence, we hypothesised that the Disinhibition scale would be positively related to BART scores.…”
mentioning
confidence: 90%
See 2 more Smart Citations